Cup texture influences taste and tactile judgments in the evaluation of specialty coffee - Carvalho, F; Fabiana, C; Spence, C (Elsevier, 2019)
It has been demonstrated previously that the surface textures of product packaging and servingware can impact the perceived taste and mouthfeel of various different foods and beverages. The present study was designed to investigate whether coffee cups with different surface textures would influence the judgment of taste and mouthfeel attributes in specialty coffee by experts (Q-graders) and amateur consumers alike. A total of 231 participants were tested in one of the three studies. A preliminary test conducted at a specialty coffee event in Russia indicated that rubbing a swatch of sandpaper whilst drinking coffee influenced perceived body and aftertaste qualities. In the two main studies (Experiment 1 for Q-graders, and Experiment 2 for amateurs), the participants evaluated a sample of specialty coffee (a different coffee in each study) served in either a smooth or a rough ceramic cup. The coffee was rated by the Q-graders as tasting significantly more acidic when sampled from the rough cup, as opposed to the smooth, whereas the amateurs perceived the coffee as being significantly sweeter when tasted from the smooth cup rather than from the rough cup instead. Both Q-graders and amateurs judged the aftertaste as significantly dryer when tasted from the rough rather than from the smooth cup. The perception of body was not significantly affected in any of the experiments. These results demonstrate that haptic cues influence the judgment of basic tastes as well as mouthfeel attributes in specialty coffee, for both experts and amateur consumers. Such results should be considered by the industry when designing innovative coatings for coffee cups. In addition to innovation, though, it is important to create cups that convey some functional and/or perceptual benefit for the coffee drinking experience.